Impacto da IFRS 15 na Qualidade dos Accruals e Gerenciamento de Resultados das Empresas Brasileiras de Capital Aberto - Souza de Souza, Paulo Vitor; Souza Gonçalves, Rodrigo; Tibúrcio Silva, César Augusto (Review of Business Management, 2022)
Purpose – To verify the effects of the mandatory nature of the new rule on revenue recognition on the quality of accruals and earnings management in publicly held Brazilian companies listed on the B3. Theoretical framework – By requiring greater judgment and discretion inassessing companies’ performance obligations, IFRS 15 can provide greater scope for managerial influence on earnings quality. Design/methodology/approach – A total of 305 Brazilian companies were used with annual data covering 2011 to 2021. As proxies for quality, the accruals quality model by Dechow and Dichev (2002) and the earnings management model by Pae (2005) were used. In addition, two models were estimated using quantile regressions to verify whether the new standard affects earnings quality. Findings – After the adoption of the standard, there is evidence of a reduction in the quality of accruals of companies in the technology sector and an increase in earnings management in general, especially in the industrialized products sector. From the research, it is possible to verify that there is evidence that IFRS 15 did not bring improvements in earnings quality in Brazilian public companies. Practical & social implications of research – Due to the failure to achieve the initial objectives expected by the implementation of IFRS 15 in Brazil, standard setters should monitor the evolution of the implications of the use of this standard, eventually seeking to improve it in the search to align the exercise of manager judgment to practices that improve the quality of accounting information. Originality/value – This study provides evidence that a new accounting standard resulted in a reduction in the quality of reported earnings, contributing to the formulation of mechanisms to improve the application of the standard, especially in the most affected sectors. Keywords: Revenues, earnings quality, earnings management, IFRS 15.